A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material
By using complex sintering and multi-layer covering technology in sodium ion batteries, to prepare high-performance sodium iron phosphate-sodium-phosphate composite materials, solve the problem of low sodium ion battery capacity, circulation and electrical conductivity, and realize more. High electrochemical properties and longer cycle life.
Patent Information
- Application Number
- CN202410047562.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The capacity, circulation and conductivity of existing sodium ion batteries are still low, making it difficult to meet higher battery usage requirements.
Use sodium bicarbonate, sodium phosphate, iron-citrate iron, iron rodate, and ammonium polarotate to compound sintered iron phosphate-sodium phosphate composite materials, and cover with sucrose and conductive carbon black grinding and citric acid The spray coverage of the aqueous solution forms a dense and solid cover film. The conductive carbon black and the nano V3GA are mixed with the cover layer to increase the conductivity.
It significantly improved the electrochemical performance of sodium ion batteries. For the first time, the capacity of the discharge gram reached 115.7ma · H/G, the 3C capacity retention rate reached 99.3%, the number of cycles reached 290 times, and the multiplier performance and cycle life were improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery materials, and particularly relates to a method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material. Background Art
[0002] Sodium-ion battery is a secondary battery that relies on the movement of sodium ions between the positive and negative electrodes to work. That is, during the charging and discharging process, sodium ions are embedded and deintercalated back and forth between the positive and negative electrodes, similar to the lithium-ion batteries commonly used on the market.
[0003] Sodium-ion batteries and lithium-ion batteries started almost at the same time. In theory, the charging time of sodium-ion batteries can be shortened to 1 / 5 of that of lithium-ion batteries, making it easier to achieve fast charging. In addition, sodium resources are abundant and cheap, and the cost of sodium-ion batteries is lower than that of lithium-ion batteries. Although the capacity of sodium-ion batteries is lower than that of lithium-ion batteries, sodium-ion batteries also have broad application prospects in areas where capacity requirements are not high, and are gradually replacing lead-acid batteries.
[0004] At present, sodium ion batteries have low electronic conductivity due to the properties of sodium ions, resulting in poor rate performance and cycle life. For this reason, carbon coating is used in this field to improve the electronic conductivity of the positive electrode material, and nitrogen, boron, sulfur and other atomic doping are used to further improve the electrochemical performance. Among them, the carbon-coated sodium vanadium phosphate positive electrode material can reach an initial capacity of about 100mA·h / g, and after 500 cycles, the capacity retention rate is about 90%. In order to further improve battery performance, a carbon-coated sodium iron phosphate-sodium vanadium phosphate composite material has been developed, with an initial capacity of about 110mA·h / g, and after 500 cycles, the capacity retention rate can reach more than 92%.
[0005] However, in order to meet higher battery usage requirements, the electrical performance of sodium-ion battery materials needs to be continuously improved and enhanced. Summary of the invention
[0006] Aiming at the problem that the capacity, cycle and conductivity of existing sodium ion batteries are still low, the present invention provides a method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material. The sodium iron phosphate-sodium vanadium phosphate prepared by composite sintering with sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate is of high quality; sucrose and conductive carbon black are used for a first ball milling coating, and then a citric acid aqueous solution is used for a second spray coating, so that the prepared coating film is more dense and firm, not easy to peel off, and the cycle life is improved; the conductive carbon black and nano V 3 The incorporation of Ga can greatly improve the conductivity of the positive electrode material and the rate performance, and the conductive carbon black and nano-V 3Ga is located in the interlayer of the coating layer, which is not affected by electrolyte corrosion, is not easy to peel off, and has high safety. The specific technical solution is as follows:
[0007] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0008] S1: Compounding sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate to obtain a mixed powder A; then sintering the mixed powder A to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0009] S2: finely crushing sodium iron phosphate-sodium vanadium phosphate into fine powder, then adding sucrose and conductive carbon black to the fine powder for low-temperature dry ball milling for 10 min to 15 min, then heating to 160° C. to 180° C. and continuing ball milling for 15 min to 20 min, and cooling to obtain ball milling coating material B;
[0010] S3: using citric acid aqueous solution as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid to obtain a coating material C;
[0011] S4: sintering the coating material C at 180° C. to 250° C. for 4 h to 8 h to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0012] In step S1 of the above technical solution, the compound is 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced; and Na is 0.3 mol% to 0.6 mol% higher than the theoretical amount.
[0013] In step S1 of the above technical solution, the sintering temperature is 600° C. to 800° C., and the sintering time is 6 h to 12 h.
[0014] In step S2 of the above technical solution, the median particle size of the micro powder is 10 um to 15 um.
[0015] In step S2 of the above technical solution, the median particle size of the sucrose and the conductive carbon black is less than 3 um.
[0016] In step S2 of the above technical solution, the mass ratio of the added sucrose and the conductive carbon black is sodium iron phosphate-sodium vanadium phosphate:sucrose:conductive carbon black=100:(0.5-1):(0.5-2).
[0017] In step S2 of the above technical solution, the temperature of the low-temperature dry ball milling is 6°C to 15°C.
[0018] In step S2 of the above technical solution, nano V is also added to the micro powder. 3 Ga, added in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: nano V 3 Ga=100:0.02~0.1.
[0019] In step S3 of the above technical solution, the mass concentration of the citric acid aqueous solution is 5% to 10%.
[0020] In step S3 of the above technical solution, the fluidized spray parameters are: the inlet temperature of the spray coating agent is 25°C to 30°C, the spray speed is 0.5L / min to 0.8L / min, the atomization pressure is 0.2MPa to 0.4MPa, and the drying temperature is 40°C to 55°C.
[0021] Compared with the prior art, the method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material of the present invention has the following beneficial effects:
[0022] 1. The method of the present invention uses sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate as composite raw materials of sodium iron phosphate-sodium vanadium phosphate. The sodium iron phosphate-sodium vanadium phosphate composite material prepared by sintering has high purity, can improve the battery charging and discharging performance and safety of use, and has high gram capacity.
[0023] 2. The method of the present invention is designed to finely grind sodium iron phosphate-sodium vanadium phosphate into micropowder, the median particle size of the micropowder is 10um-15um, and then sucrose with a median particle size of less than 3um and conductive carbon black are used for ball milling coating, wherein the conductive carbon black can adhere to the particle surface and defects of sodium iron phosphate-sodium vanadium phosphate, compensate for the surface defects of the particles, and improve the surface conductivity of the sodium iron phosphate-sodium vanadium phosphate particles. Sucrose is added to improve the firmness of the ball milling coating. When the ball mill material is ball milled at a low temperature of 6°C to 15°C, the fluidity of each powder can be improved, the sucrose can be prevented from sticking at high temperature, and the ball milling coating can be made more uniform. After uniformity, the temperature is raised to 160°C to 180°C to melt and carbonize the sucrose, so that the conductive carbon black can be well adhered to the sodium iron phosphate-sodium vanadium phosphate particles to prevent the coating from peeling off. It is designed to continue ball milling for 15min to 20min after the temperature is raised, which can ensure good bonding and coating without excessive ball milling, prevent the high sodium iron phosphate-sodium vanadium phosphate particles from producing too much fine powder, and prevent the fine powder from agglomerating too hard, so as to achieve excellent material quality.
[0024] 3. The method of the present invention uses citric acid aqueous solution to perform secondary spray coating on the ball-milled coating material, which can further improve the quality of the coating layer, make up for some defects of the sucrose and conductive carbon black coating layers, and further consolidate the firmness of the coating layer, prevent the coating layer from peeling off during subsequent charging and discharging processes, improve the cycle life, and maintain the battery efficiency for a long time.
[0025] Fourth, the coating material C is sintered at 180°C to 250°C, mainly to carbonize the citric acid to improve the conductivity, and to further carbonize the sucrose, reduce the distance between carbon layers, make the coating layer more solid, and improve the cycle life.
[0026] 5. The method of the present invention designs spray parameters according to the particle characteristics and particle size properties of sodium iron phosphate-sodium vanadium phosphate, that is, the mass concentration of the citric acid aqueous solution is 5% to 10%, the inlet temperature of the spray coating agent is 25°C to 30°C, the spray speed is 0.5L / min to 0.8L / min, the atomization pressure is 0.2MPa to 0.4MPa, and the drying temperature is 40°C to 55°C; it can achieve dense, firm and good coating of citric acid with high safety.
[0027] 6. Conductive carbon black and nano V 3 The addition of Ga can greatly improve the conductivity of the positive electrode material and improve the rate performance. 3 Ga is located in the interlayer of the coating layer and is not affected by electrolyte corrosion, is not easy to peel off, has high safety, and can ensure the battery cycle life.
[0028] In summary, the coated sodium iron phosphate-sodium vanadium phosphate composite material prepared by the present invention has good electrical performance indicators, the first discharge capacity can reach 115.7mA·h / g, the 3C capacity retention rate can reach 99.3%, the efficiency can reach 90%, and the cycle can reach 290 times. 3 After Ga, the rate performance and the number of cycles can be further improved. The coated sodium iron phosphate-sodium vanadium phosphate composite material of the present invention has good economic and practical value. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0030] Example 1
[0031] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0032] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.4 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 700° C. for 9 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0033] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 12 μm, and then sucrose with a median particle size of less than 3 μm and conductive carbon black with a median particle size of less than 3 μm are added to the micro powder in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black = 100:0.8:1.2, and low-temperature dry ball milling is performed at 10° C. for 12 min, and then the temperature is raised to 170° C. and ball milling is continued for 18 min, and the ball milling coating material B is obtained by cooling;
[0034] S3: Using 8% citric acid aqueous solution as spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 28°C, the spray speed is 0.6L / min, the atomization pressure is 0.3MPa, and the drying temperature is 50°C; and the coating material C is obtained;
[0035] S4: sintering the coating material C at 200° C. for 6 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0036] Example 2
[0037] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0038] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.5 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 600° C. for 6 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0039] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 10 μm, and then sucrose with a median particle size of less than 3 μm and conductive carbon black with a median particle size of less than 3 μm are added to the micro powder in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black = 100:0.5:0.5, and dry ball milling is performed at 6°C for 10 min, and then the temperature is raised to 160°C and ball milling is continued for 15 min, and the ball milling coating material B is obtained by cooling;
[0040] S3: Using a citric acid aqueous solution with a mass concentration of 5% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 25°C, the spray speed is 0.5L / min, the atomization pressure is 0.2MPa, and the drying temperature is 40°C; and the coating material C is obtained;
[0041] S4: sintering the coating material C at 180° C. for 4 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0042] Example 3
[0043] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0044] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.4 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 800° C. for 12 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0045] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 15 μm, and then sucrose with a median particle size of less than 3 μm and conductive carbon black with a median particle size of less than 3 μm are added to the micro powder in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black = 100:1:2, and low-temperature dry ball milling is performed at 15°C for 15 minutes, and then the temperature is raised to 180°C and ball milling is continued for 20 minutes, and the ball milling coating material B is obtained by cooling;
[0046] S3: Using a citric acid aqueous solution with a mass concentration of 10% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 30°C, the spray speed is 0.8L / min, the atomization pressure is 0.4MPa, and the drying temperature is 55°C; and the coating material C is obtained;
[0047] S4: sintering the coating material C at 250° C. for 8 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0048] Example 4
[0049] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0050] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.6 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 600° C. for 12 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0051] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 10 μm, and then sucrose with a median particle size of less than 3 μm and conductive carbon black with a median particle size of less than 3 μm are added to the micro powder in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black = 100:1:0.5, and low-temperature dry ball milling is performed at 15°C for 10 minutes, and then the temperature is raised to 180°C and ball milling is continued for 15 minutes, and the ball milling coating material B is obtained by cooling;
[0052] S3: Using a citric acid aqueous solution with a mass concentration of 10% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 25°C, the spray speed is 0.8L / min, the atomization pressure is 0.2MPa, and the drying temperature is 55°C; and the coating material C is obtained;
[0053] S4: sintering the coating material C at 180° C. for 8 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0054] Example 5
[0055] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0056] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.3 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 800° C. for 6 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0057] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 15 μm, and then sucrose with a median particle size of less than 3 μm and conductive carbon black with a median particle size of less than 3 μm are added to the micro powder in a mass ratio of sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black = 100:0.5:2, and low-temperature dry ball milling is performed at 6°C for 15 minutes, and then the temperature is raised to 160°C and ball milling is continued for 20 minutes, and the ball milling coating material B is obtained by cooling;
[0058] S3: Using a citric acid aqueous solution with a mass concentration of 5% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 30°C, the spray speed is 0.5L / min, the atomization pressure is 0.4MPa, and the drying temperature is 40°C; and the coating material C is obtained;
[0059] S4: sintering the coating material C at 250° C. for 4 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0060] Example 6
[0061] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0062] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.5 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 650° C. for 8 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0063] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 15um, and then mixed with sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black: nano V 3 Ga=100:0.6:1.5:0.05 mass ratio, add sucrose with a median particle size of less than 3um and conductive carbon black with a median particle size of less than 3um to the micropowder, perform low-temperature dry ball milling at 8°C for 10min, then heat to 165°C and continue ball milling for 20min, and cool to obtain ball milling coating material B;
[0064] S3: Using a citric acid aqueous solution with a mass concentration of 10% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 25°C, the spray speed is 0.6L / min, the atomization pressure is 0.4MPa, and the drying temperature is 45°C; and the coating material C is obtained;
[0065] S4: sintering the coating material C at 195° C. for 5 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0066] Example 7
[0067] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0068] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.4 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 800° C. for 12 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0069] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 15um, and then mixed with sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black: nano V 3 Ga=100:1:2:0.1 mass ratio, add sucrose with a median particle size of less than 3um and conductive carbon black with a median particle size of less than 3um to the micropowder, perform low-temperature dry ball milling at 10°C for 15min, then heat to 180°C and continue ball milling for 20min, and cool to obtain ball milling coating material B;
[0070] S3: Using a citric acid aqueous solution with a mass concentration of 10% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 25°C, the spray speed is 0.8L / min, the atomization pressure is 0.2MPa, and the drying temperature is 55°C; and the coating material C is obtained;
[0071] S4: sintering the coating material C at 200° C. for 6 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0072] Example 8
[0073] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0074] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.6 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 600° C. for 6 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0075] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 13um, and then mixed with sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black: nano V 3 Ga=100:0.5:0.5:0.02 mass ratio, add sucrose with a median particle size of less than 3um and conductive carbon black with a median particle size of less than 3um to the micropowder, perform low-temperature dry ball milling at 6°C for 10min, then heat to 160°C and continue ball milling for 20min, and cool to obtain ball milling coating material B;
[0076] S3: Using a citric acid aqueous solution with a mass concentration of 6% as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 26°C, the spray speed is 0.5L / min, the atomization pressure is 0.2MPa, and the drying temperature is 45°C; and the coating material C is obtained;
[0077] S4: sintering the coating material C at 180° C. for 5 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0078] Example 9
[0079] A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material comprises the following steps:
[0080] S1: Press 2NaFePO 4 ·Na 3 V 2 (PO 4 ) 3 The molecular weights of Na, Fe and V are balanced, and Na is 0.3 mol% higher than the theoretical amount. Sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate are compounded to obtain mixed powder A; the mixed powder A is then sintered at 650° C. for 10 hours to obtain sodium iron phosphate-sodium vanadium phosphate powder;
[0081] S2: Sodium iron phosphate-sodium vanadium phosphate is finely ground into a micro powder with a median particle size of 14 μm, and then mixed with sodium iron phosphate-sodium vanadium phosphate: sucrose: conductive carbon black: nano V 3 Ga=100:0.6:1.2:0.08 mass ratio, add sucrose with a median particle size of less than 3um and conductive carbon black with a median particle size of less than 3um to the micropowder, perform low-temperature dry ball milling at 8°C for 15min, then heat to 175°C and continue ball milling for 15min, and cool to obtain ball milling coating material B;
[0082] S3: Using 8% citric acid aqueous solution as spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid. The fluidized spray parameters are: the spray coating agent inlet temperature is 28°C, the spray speed is 0.7L / min, the atomization pressure is 0.3MPa, and the drying temperature is 55°C; and the coating material C is obtained;
[0083] S4: sintering the coating material C at 220° C. for 5 hours to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
[0084] The coated sodium iron phosphate-sodium vanadium phosphate composite materials (hereinafter referred to as positive electrode materials) prepared in Examples 1 to 9 were respectively made into batteries and their electrical performance was tested.
[0085] Positive electrode material slurry coating: The slurry contains 24g positive electrode material, 1g acetylene black, 3g PVDF, 2mL NMP, and water is added to adjust the slurry viscosity to 3500cP; it is coated on aluminum foil at a thickness of 16μm to make a positive electrode sheet; a metal sodium sheet is used as the negative electrode, Whatman GF / D glass fiber is used as the separator, and 1mol / L NaClO4 / EC:PC (volume ratio 1:1) is used as the electrolyte to assemble a CR2016 type button battery. Five parallel samples are made for each embodiment, and the average value is taken.
[0086] 1. Initial charge and discharge performance: The battery was charged to 4.0V at a constant current density of 0.1C, and charged to 0.05C at a constant voltage of 4.0V. After standing for 30 minutes, the battery was discharged to 2.0V at a constant current density of 0.1C.
[0087] 2. Rate performance: Charge at 0.3C current density, discharge at 0.3C / 1C / 2C / 3C rates, and record the capacity retention rate relative to 3C.
[0088] 3. Cycle performance: The battery is charged and discharged at a current density of 1C, with a voltage range of 2.0 to 4.0V and a cycle number of 90% efficiency.
[0089] The test results are shown in Table 1:
[0090] Table 1 Electrical performance test results
[0091]
[0092] From the above results, it can be seen that the positive electrode materials prepared by the methods of Examples 1 to 9 have good electrical performance indicators, the first discharge capacity can reach 115.7 mA·h / g, the 3C capacity retention rate can reach 99.3%, the efficiency can reach 90%, and the cycle can reach 290 times. 3 After adding Ga, the rate performance and cycle number are further improved.
Claims
1. A method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material, characterized in that: The steps include: S1: Compounding sodium bicarbonate, sodium hydrogen phosphate, ferric citrate, ferric vanadate and ammonium metavanadate to obtain a mixed powder A; then sintering the mixed powder A to obtain sodium iron phosphate-sodium vanadium phosphate powder; The compound is prepared according to the molecular weight of Na, Fe and V in 2NaFePO4·Na3V2(PO4)3; and the Na content is 0.3mol% to 0.6mol% higher than the theoretical amount; S2: finely crushing sodium iron phosphate-sodium vanadium phosphate into fine powder, then adding sucrose and conductive carbon black to the fine powder for low-temperature dry ball milling for 10 min to 15 min, then heating to 160° C. to 180° C. and continuing ball milling for 15 min to 20 min, and cooling to obtain ball milling coating material B; The mass ratio of the added sucrose and the conductive carbon black is sodium iron phosphate-sodium vanadium phosphate:sucrose:conductive carbon black=100:(0.5-1):(0.5-2); S3: using citric acid aqueous solution as a spray coating agent, the ball mill coating material B and the citric acid aqueous solution are fluidized sprayed to coat the surface of the particles of the ball mill coating material B with a layer of homogeneous citric acid to obtain a coating material C; S4: sintering the coating material C at 180° C. to 250° C. for 4 h to 8 h to obtain a coated sodium iron phosphate-sodium vanadium phosphate composite material.
2. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S1, the sintering temperature is 600°C to 800°C, and the sintering time is 6h to 12h.
3. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S2, the median particle size of the micropowder is 10 μm to 15 μm.
4. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S2, the median particle size of the sucrose and the conductive carbon black is less than 3 μm.
5. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S2, the temperature of the low temperature dry ball milling is 6°C to 15°C.
6. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S2, nano V3Ga is also added to the micro powder, and the added mass ratio is sodium iron phosphate-sodium vanadium phosphate: nano V3Ga=100:0.02-0.
1.
7. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S3, the mass concentration of the citric acid aqueous solution is 5% to 10%.
8. The method for preparing a coated sodium iron phosphate-sodium vanadium phosphate composite material according to claim 1, characterized in that: In S3, the fluidized spray parameters are: the inlet temperature of the spray coating agent is 25°C to 30°C, the spray speed is 0.5L / min to 0.8L / min, the atomization pressure is 0.2MPa to 0.4MPa, and the drying temperature is 40°C to 55°C.
Citation Information
Patent Citations
High tap-density lithium iron phosphate composite material and preparation method and application thereof
CN107742726A
Ferric sodium phosphate composite anode material, and preparation method and application thereof
CN109449417A